BANDUNG DIOCESE OFFICE - Zefanya, Teresa
The background of the Bandung Diocese Office project is an increase in the number of Catholics in the Diocese of Bandung. An increase in the number of people causes the need to increase the number of non-volunteer employees in the office of the Diocese of Bandung and unites all of the secretariats under the Diocese of Bandung into one building. Relocation is done as a solution to the problem of lacking space and employees in the Diocese of Bandung nowaday. The main purpose of the project of Bandung Diocese Office is to accommodate various activities in the Diocese of Bandung by adding function and space capacity in the office of the Diocese of Bandung. The second purpose of this project is designing a guest house as a place to stay for the bishop's guests as well as designing a residence for the Bandung Diocese’s pastor curia. The theme of this Bandung Diocese Office project is Religious Building in Urban Context. This theme is chosen because the project is in the middle of urban area so it has many problems such as noise, vehicle circulations, connection with surrounding buildings, and others. This theme is taken for the sake of effectivity and efficiency of the Office of the Diocese of Bandung without putting aside the Catholic or the locality value. On the other hand, the concept of Bandung Diocese Office is Reforming Religious Workplace. This concept is formulated from two things which are, first, the Catholic’s spirit which held firmly onto a tradition which have begun since more than 2000 years ago, second, the universal value which accept anyone and keep the eco-friendliness as well as open to the change of the era.